Analisa Potensi Energi Angin dengan Distribusi Weibull Untuk Pembangkit Listrik Tenaga Bayu (PLTB) Banda Aceh - Muhammad Rizal Fachri; Hendrayana Hendrayana (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Energy needs in Indonesia in particular and the world in general continue to rise due to population growth, economic growth and energy consumption patterns themselves are constantly increasing. One of the fast growing renewable energy in the world today is wind energy. Wind energy is a renewable energy that is very flexible. In general, the utilization of wind power in Indonesia is less attention. Until 2004, the installed capacity of wind power utilization is only up to 0.5 MW from 9:29 GW potential. One method used to measure the wind energy potential of wind energy for electricity generation is by using the Weibull method. From the analysis that has been carried out by the method of Weibull can be concluded that the wind energy potential of wind energy for electricity generation in Banda Aceh does not meet the eligibility criteria.